IMPLEMENTASI FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA (DSN-MUI) NOMOR: 92/DSN-MUI/IV/2014 TERHADAP PEMBIAYAAN PADA PRODUK RAHN (STUDI PADA PEGADAIAN SYARIAH CABANG PALU PLASA) - Nazil Fahmi; Nasaruddin Nasaruddin; Fadliah Mubakkirah (Tadayun: Jurnal Hukum Ekonomi Syariah, 2020)
This study aims to provide knowledge and understanding of the implementation of the National Sharia Council Fatwa of the Indonesian Ulema Council (DSN-MUI) Number: 92 / DSN-MUI / IV / 2014 concerning the financing of rahn products at the Pegadaian Syariah Branch Palu Plasa. This research was designed using descriptive research type, using a qualitative approach in data collection techniques. After the data is collected and passed the data analysis process, a conclusion is drawn using a deductive mindset. The results of this study indicate that the implementation reviewed in the Fatwa rules of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Number. 92 / DSN-MUI / IV / 2014 has stipulated that the fatwa on Financing accompanied by Rahn in all forms of financing or distribution of funds of Islamic Financial Institutions (LKS) may be guaranteed with collateral (rahn) in accordance with several provisions in the fatwa. So, financing on rahn products run by Pegadaian Syariah Branch Palu Plasa has met the provisions in the fatwa.